Model Pengelolaan Kolaboratif Dalam Pengembangan Wisata Alternatif di Area Branca Timor Leste - I Made Mardika; Anak Agung Ayu Dewi Larantika; Ni Made Jaya Senastri; Ida Bagus Udayana Putra; Leonito Reiro; Mateus Ximenes (Universitas Warmadewa, 2025)
The Branca Area in Dili, Timor-Leste, has significant potential as an alternative tourism destination through the integration of unique cultural elements, the strong religious appeal of the Cristo Rei Statue, and its scenic coastal landscape. However, tourism development in this area has not been optimal due to weak governance, limited capacity of local human resources, inadequate environmental management, and limited tourism promotion. Through a collaborative Community Service Program (Pengabdian kepada Masyarakat [PKM]) between Universitas Warmadewa and Universitade DAPAZ Timor-Leste, a collaborative tourism management model based on the pentahelix approach was designed and implemented, involving government, academics, local communities, business actors, and media. The implementation methods included literature review, situational analysis, Focus Group Discussions (FGDs), training and mentoring for institutional development (tourism awareness groups and management bodies), environmental arrangement and source-based waste management, as well as workshops on digital tourism promotion. The results indicate the establishment of a collaborative destination management body, improved environmental arrangement quality in the Branca Area, and strengthened digital promotion of Cristo Rei tourism. This model contributes as a strategic framework for the development of alternative and sustainable tourism in Timor-Leste.